INVESTIGATION OF FAILURES AND VERTICAL DISPLACEMENTS OCCURRING AT THE CHOREMI VILLAGE, NEAR THE MEGALOPOLIS’ MINES - Avramidou, E.; Psychari, E.; Kanaris, D.; Tzampoglou, P.; Loupasakis, C. (Bulletin of the Geological Society of Greece, 2016)
The current study investigates the catastrophic phenomena affecting Choremi village, at the west boundaries of the Megalopolis’ mines. For this purpose, field survey was carried out, failures in the houses were recorded, the level of aquifer was measured and soil samples were collected for the conduction of laboratory tests and mineralogy analysis. The conclusions of the investigation were verified by slope stability analysis. By evaluating all available data, it is clear that the displacements damaging the village occur due to slope failure and swelling of the clay formations of the narrow study area.